Wiley Cpa exam review impact Audios : - Hopkins, Debra (Wiley, 2005)
Wiley CPA Examination Review Impact Audios, Second Edition contains dynamic lectures on vital parts and modules of the new computerised CPA Examination. The audios are designed to facilitate memory and reinforce key concepts. They are filled with mnemonic devices, exam strategies, and a thorough review of the skills and concepts needed to pass the exam.